2018
DOI: 10.1007/s11414-018-9615-x
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of an Employment Scheme for Mentors with Lived Experience of Offending Within a Multi-Agency Mental Health Project for Excluded Young People

Abstract: The use of peer intervention schemes is increasingly popular within services for offending groups and there is growing evidence of their benefit for peers delivering the interventions. The current study explores staff and peer experiences of an employment scheme for peer mentors within a community project for young people involved in offending. Semi-structured interviews were conducted with full time staff (n=4) and peer mentors employed on the scheme (n=2). Thematic analysis revealed three themes of "Opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…In addition, studies have found that building a trusting relationship is important (Kavanagh and Borrill 2013;Matthews et al 2019;Barrenger, Hamovitch, and Rothman 2019;Thomas et al 2019) and that it may be easier for EPs to achieve this with clients due to their shared identity (Barrenger, Stanhope, and Atterbury 2017;Portillo, Goldberg, and Taxman 2017;Reingle Gonzalez et al 2019). Lastly, studies showed that EPs act as a bridge between clients and staff (Hodgson et al 2019;Barrenger, Hamovitch, and Rothman 2019) and that they make referrals or connect clients to services related to housing, mental health, education and employment (Marlow et al 2015;Portillo, Goldberg, and Taxman 2017;Thomas et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have found that building a trusting relationship is important (Kavanagh and Borrill 2013;Matthews et al 2019;Barrenger, Hamovitch, and Rothman 2019;Thomas et al 2019) and that it may be easier for EPs to achieve this with clients due to their shared identity (Barrenger, Stanhope, and Atterbury 2017;Portillo, Goldberg, and Taxman 2017;Reingle Gonzalez et al 2019). Lastly, studies showed that EPs act as a bridge between clients and staff (Hodgson et al 2019;Barrenger, Hamovitch, and Rothman 2019) and that they make referrals or connect clients to services related to housing, mental health, education and employment (Marlow et al 2015;Portillo, Goldberg, and Taxman 2017;Thomas et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, few of them had experienced this previously. Prior research suggests that nurturing environments with supportive and accepting relationships have a positive effect on recovery (De Malmanche & Robertson, 2015 ; Doroud et al, 2018 ), yet there can be challenges in forming this kind of relationship within the workplace (Tangvald-Pederson & Bongaardt, 2017 ; Hodgson et al, 2019 ). The sense of belonging can be limited at first until acceptance has been received.…”
Section: Discussionmentioning
confidence: 99%
“…The sense of belonging can be limited at first until acceptance has been received. This sense can become stronger as an individual chooses how they want to continue to belong in the workplace (Hodgson et al, 2019 ). Additionally, ambivalence can occur in wanting to be looked after and cared for, whilst also wanting professional appreciation (Tangvald-Pederson & Bongaardt, 2017 ), as indicated by the final superordinate theme in the present study, safety or ‘not a real job?’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing women with comprehensive information regarding employment agencies that focus on offender job placement can improve women’s employment outcomes, as social support from employment agencies produced positive effects for some women in our sample. Cooperation and collaboration of probation and parole departments with multiple agencies and potential employers have been shown to be helpful to offenders (Hodgson et al, 2019). Given that many women experienced structural barriers related to their offender status, building collaborative relationships between employers, employment agencies, parole and probation agents, and women under supervision can improve the efficacy of the job search process and mitigate the challenges that a criminal record presents.…”
Section: Discussionmentioning
confidence: 99%